Estruturação da comunidade de anuros e teste da hipótese do distúrbio intermediário em campos úmidos costeiros no extremo sul do Brasil - Santos, Maurício Beux dos (2016)
Environmental changes resulting from climatic conditions may limit the reproductive activity of anurans. The calling activity is an important indicator of the temporal patterns of anuran activity, which may be regulated by several factors. Reproductive strategies, including the period of calling activity, time of tadpole and juvenile recruitment, and the larval rate of development, can be used for minimizing the adverse influence of environmental variables. Moreover, local environmental changes may generate disturbances (e.g., flooding, grazing, climatic events) and alter the availability of resources in the environment, which may lead to either a reduction or an increase in the local species diversity. In this context, the intermediate disturbance hypothesis (IDH) predicts that the species diversity would be higher at intermediate levels of disturbance. In freshwater systems, for instance, water bodies with intermediate hydroperiods (temporary ponds) would have higher species diversity because they would have fewer predators in relation to permanent ponds, and more resources availability in relation to ephemeral ponds. Thus, we aimed to determine the environment abiotic effects on the calling activity of an anuran community from the temperate wetlands of the extreme southern Brazil. We identified the reproductive patterns of species considering the periods of tadpole and juvenile recruitment, the larval development rate, and the influence of environmental variables on the species activity seasonality. We also established the disturbance frequency, duration and extent in water bodies, through the investigation of the relationship between the disturbance levels, the hydroperiod and the diversity of anurans. Data were collected over 17 months in coastal wetlands of the extreme portion of southern Brazil. Between December 2012 and April 2014 we registered 11 active species, distributed in the families Hylidae, Leptodactylidae, and Bufonidae. The calling activity of the community was positively related to water temperature and rainfall. The recruitment of tadpoles occurred during the rainy period, regardless of variation in the measured abiotic variables. The recruitment of juveniles also occurred during the rainy period and was related to increased water temperature. Our results indicate a link between the frequency and duration of the disturbance with the hydroperiod, as well as with tadpole richness and abundance. Overall, much of the species abiotic dependence was linked to the patterns of reproductive behavior and phylogeny; the occurrence of many species was also linked to the hydrological regime of water bodies. Also, our study demonstrates the direct effect of a disturbance event and the IDH on the studied anuran community, in which temporary water bodies presented a richest anuran community than ephemeral or permanent ones.